PASTORAL AKHIR HAYAT: PENDAMPINGAN PASTORAL BAGI LANSIA MENGHADAPI KEMATIAN BERDASARKAN TEKS WAHYU 14:13 - Daharang, Viscka Eirene; Semuel Selanno (LIMMUD: Jurnal Ilmu Keagamaan dan Sosial Humaniora, 2024)
For some people death is something frightening. Death is considered as a separation between humans and other humans and everything they have. When you enter old age, the influence of declining physical health and the social situation around you will have a big impact on the mental health of an elderly person. Fear of death is usually felt by the elderly. This article starts from the concerns of the elderly about the arrival of death. The author's focus is the concept of the importance of Pastoral End of Life for the elderly in facing death as well as spiritual strengthening in guidance which is carried out based on the text of Revelation 14:13. The method used in this paper is library research with a qualitative descriptive analysis approach.